Analysis of the Compliance of the Actual Nutrition of Athletes during Training Camps - qizi, Ismoilova Dilnoza Zubayd (American Journal of Bioscience and Clinical Integrity, 2025)
Analysis of the overall adequacy and harmony of the main and key components of the athletes’ diet in different seasonal stages of the annual training cycle.